Leitura literária em curso de português como língua de acolhimento - Mesquita, Rebeca Kerou Teliz (2022)
The present work is the result of the action research carried out in the Professional Master's Degree in Language Teaching, at the Federal University of Pampa, Bagé/RS campus. The research theme is the literary reading of Brazilian poems from the 20th and 21st centuries in a Portuguese as a Host Language course (PHLc) for foreign students, as a strategy for learning the Portuguese language and the intercultural formation of the students. The research aims to analyze how literary reading, more specifically, the reading of poems can contribute to the acquisition of the Portuguese language, through an intercultural approach in the context of PHLc. This way, we seek to verify and analyze how literary texts are introduced in Portuguese classes for foreigners, and also, we develop a pedagogical proposal involving the reading of poems from Brazilian literature in order to implement and observe how the specificities of literature contribute to teaching of PHLc. To this end, a Literary Reading Workshop for foreigners was implemented at the Núcleo de Apoio à Aprendizagem Intercultural de Português como Língua Adicional e de Acolhimento (NAAIPLAA), which is an extension project of the Federal University of Pampa (UNIPAMPA), located inland in Rio Grande do Sul, in the city of Bagé. The classes happened through synchronous meetings on Google Meet and asynchronous through the Moodle platform. The meetings happened in a period from October to November 2021. During the course of the project, we carried out reading, speaking and writing activities. The first section of this master's thesis deals with the theoretical foundation of the research and presents studies on literature from Lajolo (2001), Reis (2003), Cosson (2009) and Eagleton (2006), in the second section we highlight the presence of literary texts in the context of Portuguese as a Foreign Language (PFL) in Takahashi's studies (2008, 2015). In the third section, we discuss the specificities of the poem through Candido (2006), Reis (2003) and Pinheiro (2007). In the fourth section, we present the perspective of Portuguese as a Host Language (PHLc) based on the theories of Tavares and Tavares (2008) and Grosso (2010). And, in the fifth section, we approach language policies from Torquato (2010), Calvet (2002) and Garcez and Schulz (2016) and in the last section we approach interculturality from the perspective of Bakhtin (1995), Franco (2019) and Janzen (2005), Walsh (2009), Xavier Albó (2005) and Almeida Filho (2002). The third chapter presents the research methodology and the proposal of the Literary Reading Workshop for Foreigners. In the following chapter, we bring the analysis of the data obtained during the application of the Workshop, for that, we examine the comments of the students during the synchronous meetings on Google Meet, as well as the students' responses in the evaluation of the Workshop through Google Forms. The fifth chapter contains the presentation of the pedagogical product that is intended for teachers as a result of the present research. In the last chapter we present the final considerations regarding the research, as we understand that through methodologies that favor pre-reading, contextualization and mediation, the foreign student develops his ability to read, interpret literary texts and build knowledge about the language.